A numerical model study of the effects of interannual time scale wave propagation on the predictability of the Atlantic meridional overturning circulation. Issue 1 (25th January 2013) - Sinha, B.; Topliss, B.; Blaker, A. T.; Hirschi, J.‐M.
Abstract: [1] We investigate processes leading to uncertainty in forecasts of the Atlantic meridional overturning circulation (AMOC). A climate model is used to supply initial conditions for ensemble simulations in which members initially have identical ocean states but perturbed atmosphere states. Baroclinic transports diverge on interannual time scales even though the ocean is not eddy‐permitting. Interannual fluctuations of the model AMOC in the subtropical gyre are caused by westward propagating Rossby waves. Divergence of the predicted AMOC with time occurs because the waves develop different phases in different ensemble members predominantly due to differences in eastern boundary windstress curl. These windstress fluctuations communicate with interior ocean transports via modifications to the vertical velocity and the vortex stretching term d w /d z . Consequently, errors propagate westward resulting in longer predictability times in the interior ocean compared with the eastern boundary. Another source of divergence is transport anomalies propagating along the Gulf Stream (and other boundary currents). The propagation mechanism seems to be predominantly advection by mean currents, and we show that the arrival of westward propagating waves can trigger development of these anomalies. The mean state of the AMOC has a small effect on interannual predictability in the subtropical gyre, most likely because eastern boundary windstress curl predictability is not strongly dependent on the state of the AMOC in the subtropics. Eastern boundary windstress curl was more predictable at 45°N when the AMOC was in a strongly decreasing state, but, unlike at 30°N, no mechanism was found linking windstress curl fluctuations with deep transports. Key Points: Predictability is longer in the ocean interior than at the boundaries Baroclinic Rossby waves cause differences in predictability Rossby waves are mainly generated by eastern boundary windstress curl